Urban Sprawl Evolution in a River-Split City: A 20-Year Analysis of Palembang - Eni Heldayani; Sumarmi Sumarmi; Syamsul Bachri; Fahrudi Ahwan Ikhsan; Wikan Jaya Prihantarto; Shida Irwana (JURNAL GEOGRAFI, 2026)
Rapid urbanization in developing countries often triggers uncontrolled urban sprawl. Palembang, the capital of South Sumatra, presents a unique case as a split city bisected by the Musi River, creating complex spatial dynamics. This research aims to uncover the spatiotemporal patterns of urban sprawl in Palembang over the last two decades (2003–2023) and analyze the direction of its physical development. The study employs a multitemporal remote sensing approach using Landsat 5, 8, and 9 satellite imagery at five-year intervals. Spatial analysis was conducted using the Normalized Difference Built-up Index (NDBI) and Modified Normalized Difference Water Index (MNDWI) to extract built-up land cover. The direction of expansion was quantified using rose diagrams to determine spatial distribution tendencies relative to the Central Business District (CBD). The results reveal a massive conversion of non-built-up land, with built-up areas increasing from 8,434.34 ha in 2003 to 15,542.36 ha in 2023. A key finding is the morphological shift from a traditional radial-centrifugal pattern to an asymmetric polycentric model. Urban growth exhibits a dominant directional bias toward the North and Northwest (Sukarami and Alang-Alang Lebar), primarily driven by infrastructure accessibility. Conversely, the Southern region (Ulu) remains stagnant due to physical wetland constraints, hydro-spatial friction, and limited connectivity. This study contributes to urban geography by establishing hydro-spatial friction as a critical determinant in urban evolution, demonstrating how natural barriers can override conventional growth models. The findings recommend Integrated Corridor Management, strict zoning policies, and transit-oriented development to mitigate the environmental impacts of low-density sprawl and promote balanced urban growth.